Music Performance Anxiety in Peruvian Music Students: Differences According to Gender, Educational Institution and Musical Genre - Chang-Arana, Álvaro-Mario (2016)
Levels of music performance anxiety (MPA) were compared in a sample of 455 Peruvian music students according to gender (males=337; females=113; missing=5), musical institution (two private and one state) and musical genre. Only gender showed an effect on MPA scores, picturing higher scores for the female group, although cultural variables could account for this difference. There were no effects of educational institution or musical genre as determined on MPA scores.